2010
DOI: 10.1108/09685221011048328
|View full text |Cite
|
Sign up to set email alerts
|

A personalized rhythm click‐based authentication system

Abstract: Purpose -In keystroke-based authentication systems, an input device to enter a password is needed. Users are verified by checking the validity of the password and typing characteristics. However, some devices have no standard desktop keyboard such as personal digital assistants and mobile phones. With these types of electronics, the system cannot successfully work in the authentication phase while the registration process is implemented based on a computer keyboard. This results in a reduction of system portab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…In the enrollment phase, a user is asked to register his/her password, and the corresponding keystroke features are recorded. Most KDA systems are used in alphanumeric‐based passwords for QWERTY keyboards . In the related literatures, a user's keystroke feature samples consist of keystroke time features such as a keystroke duration time [i.e.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In the enrollment phase, a user is asked to register his/her password, and the corresponding keystroke features are recorded. Most KDA systems are used in alphanumeric‐based passwords for QWERTY keyboards . In the related literatures, a user's keystroke feature samples consist of keystroke time features such as a keystroke duration time [i.e.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, Chang et al . employed a personal music rhythm on the basis of the user's uniqueness and consistency rather than the artificial rhythm. Users use a mouse to click their personal music rhythm directly.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Nauman and Ali [29] indicated that the adoption of text-based password on mobile devices would make the user choose simple passwords with lower security. For adopting KDA on a smart phone with a smaller screen, Chang et al [8] asked users to click the mouse in order to simulate the behavior of touch screen clicking. The personalized click feature samples generated by the mouse-clicking event were collected.…”
Section: Related Workmentioning
confidence: 99%
“…After that, we investigated the authentication utility for adopting 5,6,7,8,9, and 10 training samples. Adopting five training samples meant that the 1 st to 5 th samples were chosen as the training samples, and likewise, 6 training samples meant the 1 st to 6 th samples were selected for classifier training and so on.…”
Section: Training Sizementioning
confidence: 99%